FPGA Implementation of Park-Miller Algorithm to Generate Sequence of 32-Bit Pseudo Random Key for Encryption and Decryption of Plain Text - Bharatesh N; Rohith S (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
There are many problems arises in randomized algorithms whose solutions are fundamentally based on assumptions that pure random numbers exist, so pseudo-random number generators can imitate randomness sufficiently well for most applications. The proposed scheme is a FPGA implementation of Park-Miller Algorithm for generating sequence of Pseudo-Random keys. The properties like High speed, low power and flexibility of designed PRNG(Pseudo Random Number Generator) makes any digital circuit faster and smaller. The algorithm uses a PRNG Module, it contains 32-bit Booth Multiplier, 32-bit Floating point divider and a FSM module. After generating a sequence of 32-bit Pseudo-Random numbers we have used these numbers as a key to Encrypt 128-bit plain text to become a cipher text and by using the same key to decrypt the encrypted data to get original Plain text. The Programming is done in Verilog-HDL, successfully synthesized and implemented in XILINX Spartan 3E FPGA kit.